William Maxwell Evarts papers - Evarts, William Maxwell, 1818-1901.
Correspondence, memoranda, diary, journal, minute book, account books, printed material, and other papers concerning New York state, national, and international politics from the Civil War to the 1890s. Topics include Evarts' early law practice, cases in which he represented the U.S. during the Civil War, trial of Jefferson Davis, impeachment of Andrew Johnson, Geneva Arbitration Tribunal (1871-1872), Samuel J. Tilden election case of 1876, appointment of ambassadors, Chinese immigration, international monetary conference in Paris (1878), presidential campaign of 1880, Peabody Education Fund, Statue of Liberty, patronage, pensions, suffrage, and tariffs.
Correspondents include James Burrill Angell, John Jacob Astor, Edward Bates, James Gillespie Blaine, Joseph Hodges Choate, Cyrus W. Field, James A. Garfield, John Hay, Ebenezer R. Hoar, Levi P. Morton, Edward John Phelps, William Henry Seward, William Henry Trescott, Julia Gardiner Tyler, and Robert C. Winthrop.
Lawyer, U.S. senator from New York, and U.S. secretary of state and attorney general.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Angell, James Burrill, -- 1829-1916 -- Correspondence; Astor, John Jacob, -- 1822-1890 -- Correspondence; Bates, Edward, -- 1793-1869 -- Correspondence; Blaine, James Gillespie, -- 1830-1893 -- Correspondence; Choate, Joseph Hodges, -- 1832-1917 -- Correspondence; Davis, Jefferson, -- 1808-1889 -- Trials, litigation, etc; Field, Cyrus W. -- 1819-1892 -- Correspondence; Garfield, James A. -- 1831-1881 -- Correspondence; Hay, John, -- 1838-1905 -- Correspondence; Hoar, E. R. -- 1816-1895 -- Correspondence; Johnson, Andrew, -- 1808-1875 -- Impeachment; Morton, Levi P. -- 1824-1920 -- Correspondence; Phelps, Edward John, -- 1822-1900 -- Correspondence; Seward, William Henry, -- 1801-1872 -- Correspondence; Tilden, Samuel J. -- 1814-1886.; Trescott, William Henry, -- 1822- -- Correspondence; Tyler, Julia Gardiner, -- 1820-1889 -- Correspondence; Winthrop, Robert C. -- 1809-1894 -- Correspondence; United States. -- Department of Justice. -- Office of the Attorney General; United States. -- Department of State; Geneva Arbitration Tribunal; Peabody Education Fund; Bimetallism; Diplomatic and consular service, American; Emigration and immigration law -- United States; Patronage, Political -- United States; Pensions -- United States; Practice of law -- New York (State); Presidents -- United States -- Election -- 1876.; Presidents -- United States -- Election -- 1880.; Statue of Liberty (New York, N.Y.); Statues -- New York (State) -- New York; Suffrage -- United States; Tariff -- United States; China -- Emigration and immigration; New York (State) -- Politics and government -- 1865-1950.; United States -- Foreign relations -- 1865-1898.; United States -- History -- Civil War, 1861-1865 -- Claims; United States -- Politics and government -- 1865-1900.; Cabinet officers; Lawyers; Senators, U.S. Congress -- New York (State)